2013
DOI: 10.1556/imas.5.2013.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia in a young woman presenting with acute myocardial infarction: Case report

Abstract: Homocysteine (Hcy), a sulfur-containing amino acid that is formed by demethylation of dietary methionine to cystein. Elevated homocysteine level is known to be associated with coronary artery disease. We present a case of acute myocardial infarction in a 25-year-old woman, associated with hyperhomocysteinaemia. Her other risk factors for coronary artery disease were smoking, a moderately high LDL level, and a family history of sudden cardiac death. This case illustrates the need to include plasma homocysteine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Several cases of STEMI with HHcy have been reported since 1997 (23)(24)(25)(26)(27). The patients (4 males and 2 females) ranged in age from 25 to 36 with homocysteine levels of 31.47-187 μmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of STEMI with HHcy have been reported since 1997 (23)(24)(25)(26)(27). The patients (4 males and 2 females) ranged in age from 25 to 36 with homocysteine levels of 31.47-187 μmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple epidemiological studies have demonstrated a strong association between cardiovascular disease (CVD) and hyperhomocysteinemia [1]. However, there are limited reports of very young individuals with high homocysteine (Hcy) levels and no other risk factors, suffering an acute coronary syndrome (ACS) [2][3][4]. We herein report the case of a 23-year-old man with STelevation myocardial infarction (STEMI) having only very high Hcy levels as a risk factor.…”
Section: Introductionmentioning
confidence: 95%